PENGARUH KEPEMIMPINAN TERHADAP KINERJAPEGAWAI MELALUI BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING DI UPT PENGELOLAANPENDAPATAN PEKANBARU KOTA - Jefrianto Jefrianto; Ganarsih Lestari Raden; Suryatiningsih Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This Research aims to determined the effect of leadership on performance through organizational culture as an intervening variable at the Pekanbaru City Revenue Management Unit, Regional Revenue Agency of Riau Province, Which is located on Jl.Gajah Mada, Pekanbaru, Riau. The population in this study included all employees at the Pekanbaru City Revenue Management Unit Regional Revenue Agency of Riau Province, totaling 36 Participants.Primary data were collected using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using SmartPLS 3.0 analysis.The sampling technique chosen was the census method (36 people at the Pekanbaru City Revenue Management Unit, Regional Revenue Agency of Riau Province).The results showed that: 1) There was a significant leadership influence on the performance of the employees of UPT Pekanbaru City Revenue Management Regional Revenue Agency of Riau Province, 2) There was a significant influence of leadership on organizational culture in UPT Pekanbaru City Revenue Management Unit Regional Revenue Agency of Riau Province, 3) There was a significant influence of organizational culture on the employee performance of UPT Pekanbaru City Revenue Management Regional Revenue Agency of Riau Province, 4) There was a significant influence of leadership on employee performance through organizational culture as an intervening variable in UPT Pekanbaru City Revenue Management Regional Revenue.Keywords: Employee Performance, Leadership and Organizational Culture